The Effect of Increased Education and Health Budgets and Economic Growth on Poverty Levels During the 2007-2021 Period in South Sulawesi - Risma Risma; Abd. Rahim; Citra Ayni Kamaruddin; Diah Retno Dwi Hastuti; Sri Astuty (Universitas Islam Negeri Alauddin Makassar, 2022)
The budget allocation made by the government in the education and health sectors as well as economic growth is not enough to reduce poverty. An increase in the budget for education, health, and economic growth will reduce poverty. If the budget allocation is not right on target, it will lead to poverty. This study aims to analyze the effect of increasing the budget for education, health, and economic growth on poverty levels in South Sulawesi. The type of data used in this study is secondary data and uses time series data from 2007 to 2021. This research uses the multiple linear regression model method. The results of this study indicate that the education budget and economic growth do not affect the poverty level of South Sulawesi Province, while the health budget affects the poverty level of South Sulawesi Province. Based on the results of this study, it is hoped that the South Sulawesi provincial government will be able to proportional the education and health budget to improve the welfare of the community, especially the lower middle class.